Plasma lipids as risk factors in relapsing nephrotic syndrome - Sitti Aizah Lawang; Syarifuddin Rauf; J. S. Lisal; Husein Albar; Dasril Daud (Paediatrica Indonesiana, 2008)
Background Nephrotic syndrome is primarily a pediatric disorderand is 15 times more common in children than in adults.Relapse rate after corticosteroid discontinuation is 39 - 59%.Hyperlipidemia is an important characteristic of nephroticsyndrome. The plasma concentrations of cholesterol, triglyceride,LDL, and VLDL are increased. Persistent hyperlipidemia afterremission can be found in frequent relapse nephrotic syndrome.Objective To determine plasma lipids as risk factor for relapsingnephrotic syndrome.Methods Thirty children with nephrotic syndrome were includedin this cohort study from March 2005 until June 2007 at WahidinSudirohusodo Hospital, Makassar. Thirty children without renal diseasewere enrolled as control. Blood specimens were collected to determineplasma lipids (cholesterol, triglyceride, LDL, and HDL) levels and LDUHDL ratio. Plasma lipids were examined in the acute and remissionphases. Follow up was carried out six months after remission todetermine the occurrence of relapsing nephrotic syndrome.Results Of 30 nephrotic syndrome patients, 12 had relapsed.There were highly significant differences in total cholesterol, HDL,LDL, triglyceride, and LDL/HDL ratio between acute nephroticsyndrome and nephrotic syndrome in remission. There were nosignificant differences in cholesterol, LDL, triglyceride, LDL!HDL ratio between nephrotic syndrome in remission and control.There was also no significant difference in the incidence in relapsebetween first attack and nephrotic syndrome with more than twoattacks. Acute lipid fraction levels were not risk factors in relapsingmephrotic syndrome. Remission triglyceride level was a risk factorin relapsing nephrotic syndrome with the prevalence risk of 5.2 andCI 95% of 1.06 to 25.3.Conclusion Persistent hypertriglyceride in remission phase isassociated with an increased risk of relapse in children withnephrotic syndrome.